Do Green Accounting, Sustainable Growth Rate, and Sustainability Report Disclosure Impact the Firm-Value? - Insights from Indonesia - ., Surifah; Rofiqoh, Ifah; ., Krismiaji (Journal of Posthumanism, 2026)
In recent decades, sustainability imperatives have driven companies to move beyond a sole focus on financial performance toward environmental practices, governance, and transparency. The objective is to analyses the effects of green accounting, the sustainable growth rate (SGR), and sustainability report disclosure (SRD) on firm value. The research population comprises companies listed on the Indonesia Stock Exchange. The sample includes firms that achieved an ASEAN Corporate Governance Scorecard (ACGS) rating of 70 or higher during 2021–2023, selected using a purposive sampling method. The study analyzes data from 110 firms over the 2021–2023 period, yielding 330 firm-year observations. The results indicate that green accounting negatively affects firm value. Although this finding leads to the rejection of the related hypothesis, it can be theoretically justified and aligns with prior empirical evidence showing mixed results under varying conditions. Conversely, the sustainable growth rate and sustainability report disclosure have positive effects on firm value. These findings fully support the hypotheses and confirm prior studies as well as signaling theory, legitimacy theory, and stakeholder theory.